2005
DOI: 10.1002/jsfa.2325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding regimen and chilled storage on water‐holding capacity, colour stability, pigment content and oxidation in red deer (Cervus elaphus) meat

Abstract: The effects of feeding regimen on carcass characteristics, meat colour and lipid stability, pigment content and water-holding capacity of M. longissimus were studied in 16 male red deer. All animals were farm raised; eight were grazing pasture and eight were fed a pelleted commercial feed mixture for 10 weeks prior to slaughter. The pellet-fed deer had significantly higher live weight, carcass weight, dressing yield (g kg −1 ) and fat content than the pasture group. Carcasses from the pellet-fed deer had highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…Similar findings were reported for lamb (Díaz et al, 2002;Perlo et al, 2008) and beef (Lanari et al, 2002). Wiklund et al (2006) found that deer meat from animals fed pellets had a lower pH and greater a* values than the meat from grazing animals. The lower pH results in lower mitochondrial activity and lower oxygen consumption (Tang et al, 2005), which subsequently lead to rapid Mb oxygenation, increased blooming, and deeper penetration of the cherry-red OxyMb layer (Ramanathan et al, 2013).…”
Section: Feeding Managementsupporting
confidence: 83%
“…Similar findings were reported for lamb (Díaz et al, 2002;Perlo et al, 2008) and beef (Lanari et al, 2002). Wiklund et al (2006) found that deer meat from animals fed pellets had a lower pH and greater a* values than the meat from grazing animals. The lower pH results in lower mitochondrial activity and lower oxygen consumption (Tang et al, 2005), which subsequently lead to rapid Mb oxygenation, increased blooming, and deeper penetration of the cherry-red OxyMb layer (Ramanathan et al, 2013).…”
Section: Feeding Managementsupporting
confidence: 83%
“…Wiklund et al (2001) reported that the pH values of vacuum-packaged meat (M. longissimus dorsi) from red deer hinds, stored for 12 weeks at -1.5 o C, dropped (P < 0.001) between weeks 1 and 3, and by week 6 they returned (P < 0.001) to the level recorded in week 1. Vergara et al (2003) and Wiklund et al (2006) observed an increase in the pH of M. longissimus dorsi from red deer stored (2 o C) in a MA (40% CO 2 /60% N 2 ; 80% CO 2 /20% O 2 ; 80% CO 2 /20% N 2 ) for 23 days and under vacuum (-1.5 o C) for 12 weeks. In an experiment performed by Pollard et al (2002), the pH value of vacuum-packaged M. longissimus dorsi from red deer stags showed a steady increase over the entire storage period (5 weeks at 1 o C), while the pH of M. semimbranosus was found to increase only for the first 3 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of MAP on the quality of venison from farmed animals have also been investigated (Seman et al 1989, Wiklund et al 2001, Vergara et al 2003, Wiklund et al 2006), yet very few publications (Buys et al 1997, Paulsen et al 2005) address wild game meat from free-living animals.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the WHC value of Herik lambs (10.55%) was higher than those of fat-tailed breeds in Turkey. It was reported that carcasses with thick back fat insulated the meat and slowed down the cooling process (29). This result can be attributed to the back fat thickness of Herik lambs, which is a fat-tailed crossbreed.…”
Section: And Whcmentioning
confidence: 99%